Decision to have children from the perspective of young Malay Muslim academic women / Zuraini Jamil @Osman - Jamil @Osman, Zuraini (Division of Research and Industry Linkages , UiTM Melaka, 2014)
One issue that has been widely discussed in numerous studies in many countries, including Malaysia, as been linked to career women is motherhood. The aim of this paper is to explore what made the young female Malay Muslim academics decided to have children in their family life. Two groups of respondents with a small sample size, who work in the public universities in Kuala Lumpur and Selangor areas, have been recruited. The first group consists of ten married women and the second group includes five single female academics. I used a qualitative interview method to collect the primary data. The findings showed that all these women desired three to six children and none of them wanted to be childless. All the women also made it clear that the number of children they have had, or plan to have in future, is ideally based on several factors that they had carefully considered. The factors have been categorised into six, namely: early marriage, financial, emotional and psychological stability, religious encouragement, career commitment and the number of siblings.